Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Please help me find two independent solutions for $$3x(x+1)y''+2(x+1)y'+4y=0$$ Thanks from a new beginner into ODE's.

share|cite|improve this question
See this link – Babak S. Jan 3 '13 at 17:28
Use Frobenius method. Note that, the ode has a solution in terms of the hypergeometric function. – Mhenni Benghorbal Jan 3 '13 at 17:29
up vote 1 down vote accepted

We suppose that the $\displaystyle y=\sum_{n=0}^{\infty}a_{n}x^n$ is a solution.


$$y=a_{0}+a_{1}x+...+a_{n}x^n+... $$


$$ y''=2a_{2}+3.2a_{3}x+4.3a_{4}x^2+...+(n+2)(n+1)a_{n+2}x^n+... $$

replacing this in the DE,


we have

general term

Then we must have

$$3(n+2)(n+1)a_{n+2}+3(n+3)(n+2)a_{n+3}+2(n+2)a_{n+2}+2(n+3)a_{n+3}+4a_{n+2}=0$$ or


Now you solve this difference equation of the first order to $a_{0}=0$,$a_{1}=1$ and $a_{0}=1, a_{1}=0$. This give you two solution LI.

Note that $a_{0}$ and $a_{1}$ are the initial condition $y(0)$ and $y'(0)$

share|cite|improve this answer

Note that both $x=0, x=1$ are regular singular points( check them!). As @Edgar assumed, let $y=\sum_1^{\infty}a_nx^n$ and by writing the equation like $$x^2y''+\frac{2}{3}xy'+\frac{4x}{3(x+1)}y=0$$ we get: $$p(x)=\frac{2}{3},\; q(x)=\frac{4x}{3(x+1)}$$ and then $p(0)=\frac{2}{3},\; q(0)=0$. Now I suggest you to set the characteristic equation (see $$s(s-1)+sp(0)+q(0)=0$$ You get $s_1=0,s_2=\frac{1}{3}$. Can you do the rest from here?

share|cite|improve this answer

Since $x=0$ is a (regular) singular point of your ODE, if you want a power series solution about $x=0$, you will need to appeal to the Method of Frobenius to construct it.

This is a lengthy process, but not overly hard if you work through the tedium.

Here are some intermediate steps to help you check your work along the way:

  • The indicial equation is $r(r-1)+{2\over 3}r=0$ so the roots are $r_1=1/3$ and $r_2=0$.

  • Since $r_1-r_2\not\in\mathbb{Z}$, the situation is easier than it would have been otherwise. Two linearly independent solutions are \begin{align} y_1&=|x|^{r_1}\sum_{n=0}^\infty a_nx^n=\sum_{n=0}^\infty a_nx^{n+1/3},\\ y_2&=|x|^{r_2}\sum_{n=0}^\infty b_nx^n=\sum_{n=0}^\infty b_nx^n. \end{align}

  • To determine the coefficients for each, plug each series back into the ODE and group the coefficients by like powers to obtain a recursion formula for the $n$th coefficient. For a detailed example, see this particular example from the link above.

Hope that helps.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.